PRODUCTION OF ECO-ENZYMES FROM FRUIT PEEL WASTE AS AN EFFORT TO ADDRESS ORGANIC WASTE MANAGEMENT ISSUES IN INDONESIA - Ayu Putri Ningsih (Universitas Negeri Medan, 2023)
Based on the data from the National Waste Management Information System of the Ministry of Environment and Forestry in 2022, the waste production in Indonesia reached 54,455 tons per day. When calculated on an annual scale, Indonesia generated a total of 19.88 million tons of waste. 41.55% of this waste was composed of food scraps. One alternative to address the issue of organic waste is by processing it into eco-enzymes. Eco-enzymes are complex organic compound solutions resulting from the fermentation of organic waste, water, and sugar. The objective of this research is to produce eco-enzymes from fruit peels as a solution to organic waste management at the household level. This study is an experimental research that employs three types of substrate variations with the following formulation: water:fruit peels:sugarcane molasses = 10:3:1. The fruit peels used in creating these eco-enzymes are pineapple rinds (Ananas comosus), sweet orange rinds (Citrus sinensis), mango rinds (Mangifera indica L.), mangosteen rinds (Garcinia angostana L.), Kepok banana rinds (Musa paradisiaca Linn), rambutan rinds (Nephelium lappaceum L.), avocado rinds (Persea americana Mill), guava rinds (Psidium guajava), water apple rinds (Syzygium aqueum), cucumber rinds (Cucumis sativus), and kedondong rinds (Spondias dulcis). The research findings indicate that the fermentation process of eco-enzymes was successful. Based on the results of the organoleptic test, the characteristics of the eco-enzyme product produced in this study include a pungent and fresh aroma, and a murky brown color